APPLICATION OF THE MIRANDA PRINCIPLE IN TERMS OF PRESENTING THE LEGAL COUNSEL FOR CRIMINAL SUSPECTS IN INDONESIA - Kafrawi, Moch Faisal (Faculty of Law, Pattimura University, 2016)
This study was to determine how the application Miranda Principle in Indonesian legislation system and to find out how its implementation by law enforcement officials. Research conducted qualitatively by focus on a library study with approach of primary legal materials and secondary law. The results showed that in Indonesia, Miranda Principle set in several chapters: chapters 54, 55, 56 paragraph (1) and Article 114 Criminal Procedure Code. But in practice in some cases is still less than the maximum, especially in terms of presenting legal counsel for justice seekers who can not afford in this case the suspect / defendant.